Acute Kidney Injury in Hospitalized Children with COVID19. (1st June 2021) - Chopra, Sanya; Saha, Abhijeet; Kumar, Virendra; Thakur, Archana; Pemde, Harish; Kapoor, Dipti; Ray, Sandip; Das, Aditi; Pandit, Kaveri; Gulati, Anu; Sharma, Ankita Goel; Singh, Preeti; et al.
Abstract: Background: Acute kidney injury (AKI) has been recognized as a significant risk factor for mortality among adults with severe acute respiratory syndrome coronavirus infection. Aim: The aim of this study is to assess the prevalence and risk factors for AKI and mortality in children with coronavirus disease 2019 (COVID19) from a resource-limited setting. Methods: Cross-sectional analysis of laboratory confirmed COVID19 children admitted from 1 March to 30 November 2020 in a tertiary care hospital in New Delhi, India was done. Clinical features and associated comorbidities of COVID19 were noted. Baseline serum creatinine (height-independent Hoste's equation) and peak serum creatinine were used for staging of AKI by the 2012 Kidney Disease Improving Global Outcomes serum creatinine criteria. Univariate analysis and Kaplan–Meier survival analysis were used to compare the overall outcome in the AKI vs. the non-AKI group. Results: A total of 64 810 children between 1 month and 18 years visited the hospital; 3412 were tested for suspected COVID19, 295 tested positive and 105 (54% boys) were hospitalized. Twenty-four hospitalized children (22.8%) developed AKI; 8 in Stage 1 (33.3%), 7 in Stage 2 (29.2%) and 9 in Stage 3 (37.5%) respectively. Overall, three patients received KRT. Highest reported mortality was (66.6%) in AKI Stage 3. Risk factors for AKI included associated sepsis (OR 95% CI, 1.22-9.43, p  < 0.01), nephrotic syndrome (OR 95% CI, 1.13-115.5, p  < 0.01), vasopressor support (OR 3.59, 95% CI, 1.37–9.40, p value< 0.007), shock at presentation (OR 2.98, 95% CI, 1.16–7.60, p value 0.01) and mechanical ventilation (OR 2.64, 95% CI, 1.04–6.71, p value< 0.03). Mortality (25.71%) was higher in the AKI group (OR 95% CI, 1.14-8.35, p  < 0.023) with shock (OR 45.92; 95% CI, 3.44–612.0, p value <0.004) and ventilation (OR 46.24; 95% CI, 1.6–1333.0 p value< 0.02) as significant risk factors for mortality. Conclusion: AKI is an important modifiable risk factor for mortality in children with COVID19 in a resource-limited setting. Our study supports the strengthening of kidney replacement therapy and its timely initiation to reduce the progression of AKI and thus mortality in children.